AN ANALYSIS OF SPEECH ACT USED IN PETER RABBIT MOVIE - Revina Dwi Orizka; Ayu Oktaviani; Agus Triyogo (Universitas Islam Lamongan, 2022)
This study aimed to find out and describe the forms of speech act used in Peter Rabbit Movie. The method used qualitative design with descriptive method. Data collection techniques in this study was using the human instrument. While human instrument meant data collected by the writer itself. Techniques for analyzing the data with step by step: watched the movie, found out the speech act in dialogue of the movie, captured and identification the dialogues, and noted down the data based on the classification. The result showed, in Peter Rabbit movie the writer found 4 out of 5 classifications. There were 55 dialogues that it were representatives, 21 dialogues that it were comissives, 90 dialogues that it were directives, 61 dialogues that it were expressives.